Long-life silicon anodes by conformal molecular-deposited polyurea interface for lithium ion batteries. (1st December 2022) - Mu, Tiansheng; Sun, Yipeng; Wang, Changhong; Zhao, Yang; Doyle-Davis, Kieran; Liang, Jianneng; Sui, Xulei; Li, Ruying; Du, Chunyu; Zuo, Pengjian; Yin, Geping; Sun, Xueliang
Abstract: Establishing a stable electrode-electrolyte interface (SEI) is extremely critical to achieving a reversible silicon anode for lithium ion batteries. Herein, a conformal polyurea layer with hydrogen bonds and polar functional groups is firstly controllably constructed on the silicon electrode as an artificial SEI via molecular layer deposition. The optimized polyurea coating of ∼3 nm greatly promotes the electrochemical lithium storage performance of silicon anodes, including highly reversible cycling stability (1010 mA h g −1 after 1000 cycles) and rate capability (1820 mA h g −1 at 2 A g −1, 1420 mA h g −1 at 5 A g −1 ). Analyses show that this polyurea layer can greatly promote lithium ions diffusion kinetic in the silicon electrodes and induce a stable, thin, and LiF-rich SEI with good mechanical stability. Moreover, this polyurea coating shows a significant improvement for larger-size silicon particles (even >150 nm) and superior compatibility with ether-based electrolytes. Notably, the full cells paired with LiFePO4 cathode exhibit impressive cycling stability with a high energy density of 453 Wh kg −1 . This work provides constructive guidance for constructing a stable artificial SEI for silicon anodes. Graphical Abstract: ga1 Highlights: A conformal polyurea layer is firstly controllably constructed on the silicon electrode. Polyurea can promote lithium ions diffusion kinetic in the silicon electrodes. Polyurea can induce a stable, thin, and LiF-rich SEI with good mechanical stability. ∼3 nm polyurea layer greatly promotes the electrochemical performance of silicon anodes.